'Alien' vs. Editor: World English in the Oxford English Dictionary, Policies, Practices, and Outcomes 1884–2020. (6th September 2020) - Williams, David-Antoine
Abstract: This article discusses the changing ways in which the Oxford English Dictionary has recorded the vocabularies of 'World English'—English as spoken outside of the British Isles—from the first to the present edition. Based on direct analyses of the coded text of multiple editions, it documents and compares the practices of successive editors, taking into account various contextual factors, such as editorial principles and policies, institutional resources, and historical language development. Significant attention is given to labelling practices, including the notorious 'tramline' mark of the First Edition and Second Supplement, designating 'alien' vocabulary; the evolution of the notion of 'regional' English within the dictionary; and the contributions of technology to the art of lexicography. The final section details changes in policy and methods in the current revision and expansion, evaluating both its practices vis-à-vis its predecessors, and the picture it gives us of the current state of World English.